The 2008 Food Crisis as a Critical Event for the Food Sovereignty and Food Justice Movements - Shawki , Noha (The International Journal of Sociology of Agriculture and Food, 2012)
As a reaction to the 2008 food crisis, a diverse group of US-based organizations formed a multi-sectoral coalition to promote food sovereignty. How did the 2008 food crisis unify these diverse groups? How did different groups with different agendas find a common cause in food sovereignty? I draw on social movement theory to explain the formation of the coalition and show how its member groups have sought to strengthen its capacity, formulate a coherent message, and jointly campaign for change in food and agriculture policy. I find that a number of variables explain these processes: heightened threats and expanding opportunities encourage initial joint mobilization, while pre-existing ties and trust, organizational flexibility, and frame alignment help expand the membership and capacity of the coalition.